2019
DOI: 10.15171/ijhpm.2019.106
|View full text |Cite
|
Sign up to set email alerts
|

Health-Seeking Behaviors and its Determinants: A Facility-Based Cross-Sectional Study in the Turkish Republic of Northern Cyprus

Abstract: Background: Understanding health-seeking behaviors and determining factors help governments to adequately allocate and manage existing health resources. The aim of the study was to examine the health-seeking behaviors of people in using public and private health facilities and to assess the factors that influence healthcare utilization in Northern Cyprus. Methods: A cross-sectional study was conducted in 2 polyclinics among 507 people using a structured intervieweradministered questionnaire. Health-seeking b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 33 publications
3
33
0
Order By: Relevance
“…The study done in the Turkish Republic of Northern Cyprus also identified that smoking increases the odds of HSB. 31 Having CBHI coverage plays an important role in the HSB of the elderly. Hence, not having CBHI coverage…”
mentioning
confidence: 99%
“…The study done in the Turkish Republic of Northern Cyprus also identified that smoking increases the odds of HSB. 31 Having CBHI coverage plays an important role in the HSB of the elderly. Hence, not having CBHI coverage…”
mentioning
confidence: 99%
“…highly educated older adults, richest older adults, and urban older adults were more likely to opt for a routine medical check-up than their counterparts. Furthermore, older adults with some chronic diseases were more likely to opt for a routine medical check-up than their counterparts [29].…”
Section: Discussionmentioning
confidence: 99%
“…A study examining ethical differences in participation in medical check-ups among the elderly found a higher prevalence of routine medical check-up among Malay (59.68%), Chinese (60.85%), and Indian population (68.07%), respectively [26]. Abuduxike et al (2020), in their study, noticed that half of the participants (51.7%) in Northern Cyprus visited the health center for a routine medical check; however, these participants were previously associated with some medical conditions. Routine medical check-up varied by various background characteristics;…”
Section: Discussionmentioning
confidence: 99%
“…Although this provision offers healthcare coverage to everyone, it does not give any indication of the quality, accessibility and availability of the healthcare services. Although the constitution of North Cyprus accords equal rights to everyone to benefit from public healthcare services, it is not applicable because there is a high share of out-of-pocket payment for health services in North Cyprus [ 16 , 19 ].…”
Section: Introductionmentioning
confidence: 99%